2015
DOI: 10.1016/j.ympev.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of squirrel monkeys (genus Saimiri): South-central Amazon origin and rapid pan-Amazonian diversification of a lowland primate

Abstract: The squirrel monkey, Saimiri, is a pan-Amazonian Pleistocene radiation. We use statistical phylogeographic methods to create a mitochondrial DNA-based timetree for 118 squirrel monkey samples across 68 localities spanning all Amazonian centers of endemism, with the aim of better understanding (1) the effects of rivers as barriers to dispersal and distribution; (2) the area of origin for modern Saimiri; (3) whether ancestral Saimiri was a lowland lake-affiliated or an upland forest taxa; and (4) the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 51 publications
8
92
1
Order By: Relevance
“…Our work shows that the rivers indeed act as barriers restricting gene flow (Cowman & Bellwood, ; Naka & Brumfield, ). However, with the divergence times of each river varying, and the relative divergence times differing between species, our work supports the contention that the barriers represented by rivers may be much more dynamic than classic views of vicariant histories promoted by river formation (Lynch et al, ; Ribas et al, ). Moreover, by detailing how genetic divergence varies temporally, spatially and across taxa, our work lends support to the hypothesized proposal of cyclical periods of connections and isolations (i.e.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Our work shows that the rivers indeed act as barriers restricting gene flow (Cowman & Bellwood, ; Naka & Brumfield, ). However, with the divergence times of each river varying, and the relative divergence times differing between species, our work supports the contention that the barriers represented by rivers may be much more dynamic than classic views of vicariant histories promoted by river formation (Lynch et al, ; Ribas et al, ). Moreover, by detailing how genetic divergence varies temporally, spatially and across taxa, our work lends support to the hypothesized proposal of cyclical periods of connections and isolations (i.e.…”
Section: Resultssupporting
confidence: 83%
“…The role of rivers in preventing gene flow and promoting diversification is supported by the existence of AoEs, such as those delimited by the borders of major Amazonian rivers, and which are supported by diversity patterns of different taxonomic groups (Fernandes et al, ; Godinho & da Silva, ; Lynch Alfaro et al, ). Our work extends these findings to population divergence of frogs and lizards, but we cannot predict if the observed genetic structure of D. leucophyllatus and G. humeralis associated with river barriers could promote speciation in these taxa over time (Sukumaran & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these authors concluded that this genus comprises only three species, S. oerstedi , S. sciureus , and Saimiri vanzolinii , which diversified during the Pleistocene. This is consistent with the estimate of Alfaro et al (2015), who concluded that S. boliviensis diverged from the other Saimiri species less than 1.5 Ma.…”
supporting
confidence: 92%
“…This genus is distributed primarily in the Amazon basin and Guianas (Figure 1), except Saimiri oerstedii , which is found in Central America, Costa Rica and Panama (Chiou et al , 2011). One of the most recent biogeographical studies of Saimiri (Alfaro et al , 2015) indicated that the species diversity of the genus is the product of a recent pan-Amazonian radiation. Based on the 14 clades identified in the analysis of the mitochondrial DNA (D-loop and cytb), these authors suggested a provisional taxonomy consisting of S. sciureus , S. oerstedii ( S. o. oerstedii and S. o. citronellus ), S. collinsi , S. ustus (A, B, and C lineages), S. boliviensis, S. cassiquiarensis ( S. c. cassiquiarensis, S. c. albigena, S. c. macrodon A, S. c. macrodon B, and S. c. macrodon C), and S. vanzolinii .…”
mentioning
confidence: 99%
“…This formation could have similarly influenced capybaras. The HRCH seems to play a fundamental role in the diversification process of numerous avian taxa [11,[204][205][206][207][208][209] and some Primates taxa [110,210]. The temporal splits obtained with the MNJ procedure could also support the RH, because glacially-driven diversification mainly occurred within the last 0.9-0.02 MYA.…”
Section: Miocene and Pliocene Amazon Biodiversity Hypotheses For The mentioning
confidence: 95%